Profile of self-medication among university students of health courses in northeastern Brazil (Revista Contexto & Saúde, 2023)
This study aimed to know the self-medication profile among university students in the health area of a public educational institution. This is observational research with a cross-sectional design, carried out with the students of the courses of Nursing, Pharmacy, Physiotherapy, Speech Therapy, Medicine, Nutrition, Dentistry, and Occupational Therapy of the Federal University of Sergipe (UFS), Campus Lagarto. An instrument adapted from the Coelho study (2017) containing 29 questions about sociodemographic data and the practice of self-medication was used. Data were collected from December 2020 to March 2021. The questionnaire was sent to participants through the Google Forms app. The data were analyzed using descriptive and inferential statistics at the significance level of p < 0.05. Among the participants (n=210), it was found that 97.14% (n=204) of the students had already practiced self-medication, despite knowing the risks of such practice. Headache was the most managed complaint by self-medication (85.78%; n=175) and the most used pharmacological classes were analgesics (90.69%; n=185) and anti-inflammatory drugs (48.53%; n=99). Self-medication was performed with the use of old prescriptions (54.41%; n=111) and by the knowledge acquired during graduation (53.92%; n=110). The main source of information was the medicine package leaflet (81.37%; n=166). Therefore, self-medication is an expressive practice among university students in the health area, which requires awareness and understanding about the positive and negative implications of this practice for the future patients of these university students.
Keywords: Self-care; Self-medication; Higher education; Students.